The Actualization of Political Communication Deliberative Democracy of DPRD Medan Produces Gender Responsive Policies - Beby Masitho Batubara; Rehia K. Isabella Barus; Taufik Walhidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Gender injustice is one of the main problems in Medan City, problems experienced by women in various problems including marginalization, patriarchal cultural factors, violence, human trafficking, and the position of women in the political realm. Women's problems can be solved with gender responsive public policies. DPRD as the manifestation of the people's voice, has a central role in realizing gender pengarustamaan by producing gender responsive policies. The policies produced by the Medan City DPRD from period to term of office of DPRD members do not produce gender responsive policies, one of the factors causing the weak political communication. Weak political communication between legislative members, local government NGOs / CSOs and constituents. Whereas the interest group in producing a policy should have the obligation to convey ideas / issues summarized from various problems that occur in society, especially women in Medan City. The problem of weak political communication which results in the lack of gender responsive policies is the basis for the importance of alternative models of political communication in producing gender responsive policies. This study uses empirical methods with qualitative analysis followed by FGDs involving stakeholders, participatory, participatory, democratic political communication models that involve all interest groups by producing shared understanding and the best solutions in producing gender responsive policies.